Convergence Properties of (μ + λ) Evolutionary Algorithms - Ter-Sarkisov, Aram; Marsland, Stephen (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
We present a number of convergence properties of population-based Evolutionary Algorithms (EAs) on a set of test functions. Focus is on EA using k-Bit-Swap (kBS) operator. We compare our findings to past research.